In vitro Assay Revealed Mismatches between Guide RNA and Target DNA can Enhance Cas9 Nuclease Activity - Luan, Ji; Li, Zhen; Wang, Hailong; Fu, Jun; Zhang, Youming (Current Chinese Science, 2021)
Background: CRISPR-Cas9 is a powerful technology that allows us to modify DNA sequences in a specific manner across a variety of organisms. Due to its high efficiency and specificity, and ease of use, it becomes a commonly used method for gene editing. Although many structural and biochemical studies have been carried out to understand the fundamental mechanism of CRISPR/Cas9, our understanding of CRISPR/Cas9 caused off-target effects is still lacking. Methods: The enhanced in vitro cleavage activity of Cas9 protein from Streptococcus pyogenes (SpCas9) was evaluated by both synthetic crRNA-tracrRNA duplexes and in vitro transcribed single guide RNAs. Results: Here, we report an unexpected finding that mismatches between the guide RNA and target DNA significantly enhanced the in vitro cleavage activity of SpCas9 by more than 2 folds. Conclusion: Our observation that mismatches between the guide RNA and target DNA can dramatically increase the in vitro cleavage of Cas9 suggests the potential sequence preference for the CRSIPR/Cas9 system.
Keywords: CRISPR